UV-induced photolysis of polyurethanes - Petit, Charlotte; Bachmann, Julian; Michalek, Lukas; Catel, Yohann; Blasco, Eva; Blinco, James P.; Unterreiner, Andreas-N.; Barner-Kowollik, Christopher (Chemical Communications, 2021)
Waste production associated with the use of non-degradable materials in packaging is a growing cause of environmental concern, with the polyurethane (PU) class being notorious for their lack of degradability. Herein, we incorporate photosensitiveortho-Nitrobenzyl units into PUs to achieve controllable photodegradability. We performed their photolysis in solution and thin films which can inform the design of degradable adhesives.
CRIS-Team Scopus Importer:2022-04-14